The Effectiveness of English Learning Through Online Learning During the Covid-19 Pandemic - Idawati Situmorang; Rajainal Saragih; Yumitra Falenthine Br Ginting (International Journal of Educational Research Excellence (IJERE), 2020)
The aims of this study are: (1) To find out the online learning used by English teachers in the classroom; (2) to find out whether the online learning used by the teacher is effective in learning English in elementary schools. This research is a classroom action research, which is usually abbreviated as CAR. The research was carried out in the fourth grader of SD Negeri 016528 Pasir Mandoge. The samples taken are the fourth grader of  SD Negeri  016528 with a total of 26 students. The technique used in data collection is using a questionnaire. The data collection instrument used a questionnaire containing the types of closed, semi-closed, and open questions distributed using a google form. The results of the study can be concluded that the implementation of online learning that is carried out optimally can increase student activity and learning outcomes in English subjects in the fourth grade in elementary school. This can be seen from the number of students who are in the active category as much as 50% and the very active 7.692%, so the number of student activities is 57.692%. In the second cycle, there was an increase in students who were in the active category as much as 45.154% and those who were very active experienced an increase to 38.463%.d important findings.